A very early clinical response to treatment with the Janus kinase inhibitor tofacitinib in patients with active rheumatoid arthritis: the dynamics of pain and central sensitization elements - A. E. Karateev; E. S. Filatova; E. Yu. Pogozheva; V. N. Amirdzhanova; E. L. Nasonov; A. M. Lila; V. I. Mazurov; A. Yu. De; A. A. Baranov; N. A. Lapkina; G. V. Lukina; N. A. Kiryukhina; et al. (Современная ревматология, 2020)
Janus kinase (JK) inhibitors block the intracellular signaling pathways that are responsible for the synthesis of proinflammatory cytokines and mediators, which in turn cause the activation of pain receptors and central sensitization (CS). It is suggested that JK inhibitors can rapidly eliminate pain and reduce the severity of CS.Objective: to evaluate the effect of the JK inhibitor tofacitinib (TOFA) on the intensity of pain and the signs of CS in patients with active rheumatoid arthritis (RA) at 7 and 28 days after therapy initiation.Patients and methods. A study group consisted of 39 patients (79.5% female) (mean age 50.9±11.1 years) with RA (DAS28 5.8±0.6). Of these, 89.7% were seropositive for rheumatoid factor; 82.0% took methotrexate and 18.0% received leflunomide. All the patients were prescribed TOFA 5 mg twice daily due to the inefficacy or intolerance of biological agents. The investigators estimated pain intensity using a Brief Pain Inventory (BPI), rated the presence of a neuropathic pain component (NPC) with the PainDETECT questionnaire, and assessed the signs of CS with the Central Sensitization Inventory (CSI) during the first 4 weeks after TOFA administration.Results and discussion. The patients initially experienced moderate or severe pain (the mean scores of 5.33±2.51 on the numerical rating scale (NRS) included in BPI); 53.8% had signs of CS (CSI scores of ≥40); 17.9% had signs of a NPC (PainDETECT scores of >18). Already on day 7 after the start of TOFA administration, there was a statistically significant decrease in the mean NRS pain intensity scores to 4.06±2.2 (p=0.01) and by 29.4±17.9%, as shown by the patient's assessment of the analgesic effect of therapy (BPI), as well as the severity of CS, namely a decrease in the mean NRS pain score to 35.9±11.2 (p=0.01). On 28 days, the effect became better: there was a reduction in the level of NRS pain to 2.32±1.57 (p<0.001), in pain according to the patient's assessment of the analgesic effect of therapy to 43.6±29.6%; in the median PainDETECT score to 2.5 [0; 8.7] (p<0.001); and in CSI scores to an average of 26.4±13.9 (p <0.001). No serious adverse reactions were noted.TOFA has a rapid analgesic effect, which allows it to be considered as a chooser for pathogenetic therapy in patients with active RA and severe pain, especially in the presence of CS signs and secondary fibromyalgia. Undoubtedly, large-scale, long-term controlled studies with a wider range of estimated parameters are required to clarify the therapeutic potential of TOFA in this patient category. The limitation of this investigation was its open observer design pattern.Conclusion. The use of the JK inhibitor TOFA can achieve a rapid analgesic effect, inter alia due to its effect on CS and NPC.